Fetal macrosomia Maternal and Perinatal outcome - Al - Wazzan*, Raida Muhammed; Sarsam, Samar Daoud (AL-Kindy College Medical Journal, 2011)
Background: Fetal macrosomia represent a continuing challenge in obstetrics and increasing in it’s occurrence as well as it is associated with maternal and perinatal complications. Objective : To determine the maternal and perinatal outcome related to fetal macrosomia. Design: A prospective case control study. Patients and methods) :10th March-31st May, 2006 A prospective case control study had done over the period from 10th March to 31st May, 2006 in Al-Batool maternity teaching hospital in Mosul city .The study group consisted from 633 singleton alive newborns with gestational age ≥37weeks weighing 4000 grams and heavier and mothers of these newborns compared with control group which consisted from 4155 singleton alive newborn with gestational age ≥37weeks weighing 2500-3999 grams and mothers of these newborns .The obstetrical outcome variables which compared between the two groups include mode of delivery, indication of caesarean section and maternal and perinatal complications. Results : Macrosomic newborns (≥4000grams) delivered in this study account for (12.45%) of total deliveries. Newborns with a birth weight of ≥4500grams constitute 2.65% from all deliveries .Male Newborns (65.24%) was higher and statistically differed among the study group (p value=0.001). Instrumental vaginal delivery (P value=0.010,Odd ratio :2.12, 95 %CI :1.19-3.76) and cesarean section delivery (P value=0.000,Odd ratio:1.63, 95 %CI : 1.34-1.98), mainly the emergency cesarean section (18.79%), were significantly different among the study group .Failure of progress of labour and cephalopelvic disproportion were the main indications in study group and showed statistical significant difference between the two groups. Among the study group, there was neither maternal death nor uterine rupture but there was higher occurrence of postpartum hemorrhage, genital tract trauma and shoulder dystocia which were significantly different when it compared with control group .Erb’s palsy was the main perinatal complication and was statistically different among macrosomic group (P value=0.000) . Conclusion: Fetal macrosomia was associated with higher rate of instrumental vaginal delivery and caesarean section mainly due to failure of progress of labour and cephalopelvic disproportion .There were higher rate of postpartum haemorrhage, genital tract trauma as well as shoulder dystocia with neither maternal death nor uterine rupture in study group . Among macrosomic newborn, Erb’s pulsy was the main perinatal complication